28-Day inhalation toxicity of graphene nanoplatelets in Sprague-Dawley rats. Issue 7 (8th August 2016) - Kim, Jin Kwon; Shin, Jae Hoon; Lee, Jong Seong; Hwang, Joo Hwan; Lee, Ji Hyun; Baek, Jin Ee; Kim, Tae Gyu; Kim, Boo Wook; Kim, Jin Sik; Lee, Gun Ho; Ahn, Kangho; Han, Sung Gu; et al.
Abstract: Graphene, a two-dimensional engineered nanomaterial, is now being used in many applications, such as electronics, biological engineering, filtration, lightweight and strong nanocomposite materials, and energy storage. However, there is a lack of information on the potential health effects of graphene in humans based on inhalation, the primary engineered nanomaterial exposure pathway in workplaces. Thus, an inhalation toxicology study of graphene was conducted using a nose-only inhalation system for 28 days (6 h/day and 5 days/week) with male Sprague-Dawley rats that were then allowed to recover for 1-, 28-, and 90-day post-exposure period. Animals were separated into 4 groups (control, low, moderate, and high) with 15 male rats (5 rats per time point) in each group. The measured mass concentrations for the low, moderate, and high exposure groups were 0.12, 0.47, and 1.88 mg/m 3, respectively, very close to target concentrations of 0.125, 0.5, and 2 mg/m 3 . Airborne graphene exposure was monitored using several real-time instrumentation over 10 nm to 20 μm for size distribution and number concentration. The total and respirable elemental carbon concentrations were also measured using filter sampling. Graphene in the air and biological media was traced using transmission electron microscopy. In addition to mortality and clinical observations, the body weights and food consumption were recorded weekly. At the end of the study, the rats were subjected to a full necropsy, blood samples were collected for blood biochemical tests, and the organ weights were measured. No dose-dependent effects were recorded for the body weights, organ weights, bronchoalveolar lavage fluid inflammatory markers, and blood biochemical parameters at 1-day post-exposure and 28-day post-exposure. The inhaled graphenes were mostly ingested by macrophages. No distinct lung pathology was observed at the 1-, 28- and 90-day post-exposure. The inhaled graphene was translocated to lung lymph nodes. The results of this 28-day graphene inhalation study suggest low toxicity and a NOAEL of no less than 1.88 mg/m 3 .